STRATEGIC DIRECTIONS FOR STRENGTHENING THE PSYCHOPHYSICAL STATE OF SCHOOLCHILDREN BY INCREASING THE LEVEL OF PHYSICAL ACTIVITY IN THE CONTEXT OF SOCIAL CHANGE AND MARTIAL LAW (Physical Culture and Sport: Scientific Perspective, 2024)
The article is devoted to the problem of ensuring a minimum level of physical activity among schoolchildren in the current conditions of social challenges, particularly during the period of recovery from the COVID-19 pandemic and during martial law in Ukraine. The article analyses the main factors influencing the decline in physical activity among schoolchildren. In addition, it is emphasized that existing physical education programs only partially address these problems, which requires the development of new methods, tools, and approaches to this process.The main purpose of the article is to identify effective means and methods that will help improve the physical condition of schoolchildren and their psychological well-being in the current conditions. The tasks of the study are highlighted, including the search for and substantiation of methods to increase the integration of physical activity into the educational process of general secondary education institutions.To increase the level of physical activity of students in schools, it is necessary to introduce innovative teaching methods. The recommendations include changing physical education programs, taking into account the psychological state of students, and introducing them to the educational preparation of future teachers to work in the modern world.As part of the study, we identified strategic directions for increasing physical activity in the educational environment of schoolchildren. These strategic directions include changing educational programs, introducing better teacher training, creating more inclusive sports programs, and much more. These areas represent a comprehensive approach to engaging students in an active lifestyle. This includes working with local sports clubs and using digital technologies to improve access to exercise.The paper concludes with a recommendation to change the approach to physical education, taking into account the post-conflict period and martial law in Ukraine. The authors emphasize the need to develop comprehensive programs and strategies that would meet the current learning environment and promote healthy lifestyles among schoolchildren. Further research in this area should be aimed at assessing the effectiveness of the innovations implemented and their adaptation in times of war.
Keywords: physical activity; schoolchildren; strategic directions; COVID-19; martial law